Complete duodenal necrosis associated with non-traumatic duodenal hematoma requiring emergent pancreatico-duodenectomy. (2020) - Koichopolos, Jennifer; Keow, Jonathan; Parfitt, Jeremy; Yoshy, Cathy; Wiseman, Daniele; Leslie, Kenneth
Highlights: Duodenal hematoma and necrosis should be recognized as part of the spectrum of consequences of acute pancreatitis. Surgical management is complex and challenging. General surgeons should have a surgical approach to this complication whether that be diversion or definitive resection. Definitive resection should be completed in multiple steps if there is extensive necrosis and the patient is clinically unwell. Abstract: Introduction: Duodenal necrosis is a rare complication of acute pancreatitis but can occur given the shared blood supply to the head of the pancreas and the duodenum. Presentation of case: A 55-year-old male presented with acute-on-chronic pancreatitis and a duodenal hematoma. The hematoma expanded to occlude the biliary tree and, shortly after, the duodenum necrosed and perforated. The patient required an emergent pancreaticoduodenectomy performed in two stages. Discussion: Surgical management is complex and a difficult challenge for a general surgeon. Many advocate for wide drainage to create a controlled fistula using a malecot through the wall defect/separate duodenotomy/a retrograde jejunostomy tube. This case represents an extreme variation on this issue which was best managed by definitive resection given the extent of the necrosis. Conclusion: This case report demonstrates that duodenal hematoma and necrosis should be recognized as part of the spectrum of consequences of acute pancreatitis. General surgeons should have a surgical approach to this complication whether that be diversion or definitive resection.